Ethylene absorber (KMnO4) in postharvest quality of pinha (Anona squamosa L.) - Sanches, Alex Guimaraes [UNESP]; Silva, Maryelle Barros da; Silva Moreira, Elaine Gleice; Santos, Edmarcos Xavier dos; Paiva Menezes, Keren Railka; Martins Cordeiro, Carlos Alberto (United Arab Emirates Univ, 2019)
The ripening pattern of the climacteric type of the pinha (Anona squamosa L.) limits its shelf life at room temperature, in addition, storage at low temperatures develops cold sores on the fruit. Thus, the association of conservation technologies is fundamental to reduce the losses in the post-harvest of this fruit, so it was aimed to evaluate sachets impregnated with potassium permanganate (KMnO4) associated with refrigeration in the control of ripening and preservation of quality. For this, pinhas were harvested at physiological maturity, packed in polystyrene styrofoam trays coated with PVC film with and without the presence of sachets containing 3 g of KMnO4 and stored at 13 degrees C for 20 days. Every five days the fruit quality was evaluated as: weight loss, cracking index, firmness, external appearance, starch content, soluble solids, titratable acidity, pH, ratio SS/TA, coloring (Hue, Chroma and Luminosity) and cold damage. The absorption of ethylene by the KMnO, sachet inside the packages preserved significantly (p <0.05) the physical-chemical quality and the visual appearance of the fruits but did not influence the coloration (chroma and luminosity) and incidence of damage by cold in relation to its control at the end of the storage period. The packing of pinhas containing 3 g of KMnO4 is an alternative to delay ripening, prolong the shelf life without compromising the physical-chemical quality of the fruits.
Keywords: Anona squamosa L.; Physical-chemical quality; Potassium permanganate; Refrigeration